The choice of English pronunciation goals: different views, experiences and concerns of students, teachers and professionals. Issue 3 (2nd September 2019) - Chan, Jim Yee Him
Abstract: This study examined the choice of English pronunciation goals by Hong Kong's major stakeholders (i.e. professionals, teachers and students) via semi-structured individual/focus group interviews. 146 participants reported on their English use experience and explained their choice among three targets, namely a native speaker (NS) target, an educated local target and a target focusing on intelligibility. The findings revealed the participants' differing views and concerns surrounding four factors determining their choices (i.e. people's experience of language use, the status and pragmatic value of the language goal, its perceived attainability and intelligibility). Despite the professionals' greater experience with international communication, most of them regarded NS pronunciation as their target because of its high pragmatic value. Although some students and teachers acknowledged the importance of maintaining mutual understanding, their choice seemed to be restricted by the NS-oriented assessment criteria. This study concludes by discussing the implications of the research findings for pronunciation teaching.